Growth and volatile compounds of Martianthus leucocephalus exposed to heavy metal stress - Jesus,Daniel da Silva de (2016)
ABSTRACT: Martianthus leucocephalus is found in the semi-arid Northeast of Brazil and has high pharmacological potential due to the production of volatile compounds. This study aimed to evaluate the Cd (15, 30, 45 and 60µmol L-1), Cu (30, 60, 90 and 120µmol L-1) and Zn (150, 300, 450 and 600µmol L-1) levels on the growth of this species and its volatile compounds production. Apical cuttings were placed in plastic trays containing 6.0L nutrient solution, and after rooting, they were submitted to Cd, Cu and Zn treatments for 15 days. All the metals evaluated reduced the succulence and growth of all parts of M. leucocephalus . This effect was accompanied by the increase of Cd, Cu and Zn concentrations in all plant tissues. Volatile compounds content produced by M. leucocephalus was increased only by Zn (86%).